(1192) The Application of The Theory of Growth in Socialist Economy to Developing Countries - Alexander Muller (معهد التخطيط القومى, 2026)
The general conditions for socio-economic development in developing countries do not make it possible to present a universal type of growth adjustable to the needs of different groups of countries. But in spite of this, there is a necessity to determine some common problems of these countries to research the phenomena which regularly and continuously are existing in all developing economies. One of the regular processes of development is the economic growth, conditioning to permanent increase of production and of consumption of the population, as well.